Dosimetric Analysis of 6 MV Energy Photon Radiation Beam on Flatness and Symmetry on Linac in Radiotherapy Installation of UNAND Hospital - Analia, Rika; Fardela, Ramacos; Ridwan, Ridwan; Diyona, Fiqi; Muttaqin, Afdhal (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
A dosimetric analysis of a 6 MV photon energy radiation beam on flatness and symmetry in LINAC radiotherapy at UNAND Hospital has been conducted. The aim was to measure the quality of the photon beam using an ion chamber cc 13 detector by observing the beam profile and analyzing the effect of field size and irradiation depth. This study used a blue phantom as the object of irradiation with 6 MV photon energy and variations in irradiation field size.  The results showed that the PDD curve at 6 MV energy was by the international standard recommended by BJR-25. Then, the average values of flatness and symmetry in the field area of 10×10 cm2 and 15×15 cm2 are 1.6% and 2.4% for flatness and 2.3% and 1.9% for symmetry. Thus, the dose distribution is more uniform, and both the left and right sides of the profile on the center axis appear balanced, which will help deliver the dose to the patient better. Thus, these values are suitable for clinical use. This study found that the beam profile was larger on the left side of the main axis. This must be considered to ensure the dose distribution complies with the established safety standards. The results also show that variations in the field area and irradiation depth can affect the beam profile, and the resulting flatness and symmetry values are in accordance with the IAEA TRUS-381 and AAPM TG-142 recommendation standards, which are ±2% flatness and ±3% symmetry.